Machiavelli’s Ethics on Expansion and Empire - Vavouras, Elias (Conatus - Journal of Philosophy, 2023)
Machiavelli believes that the expansion of a state is inevitable. Human affairs are characterized by constant movement and change, and expansion is the necessary stage of a state moving towards its prosperity. But there are historical examples of states that tried to stand stable for centuries and resist movement and expansion, but ultimately failed, because they were not prepared to grow by themselves or to deal with the growth of their enemies. This article tries to interpret the Machiavellian arguments that support the thesis that the expansion of a state is inevitable and argue that its entrenchment within its borders is something contrary not only to the nature of human affairs but also to the proper constitution of the state. Also, the crucial question is whether Machiavelli’s positions have ethical foundations rooted either in human natural right or in the modes or means of expansion. From this point of view, the terms hegemony and empire acquire a different meaning and a different moral dimension.